Mechanism Design and Motion Optimization of the Flip Mechanism of Glass Loading Machine - Lv Kun; Yan Minghui; He Lifang (Jixie chuandong)
The glass loading machine is important equipment which generally uses four-bar mechanism to flip a piece of glass,and the mechanism decides the motion performance of the glass loading machine.According to the working space constraints and motion requirement,the initial position conditions of the flip mechanism is got and based on it the structure design is conducted by the rigid body guidance method for mechanism design,and the reasonable structure size is given.The mechanism motion simulation model is built with the ADAMS software,and then the motion characteristics of the mechanism is analyzed based on the simulation result when input a uniform motion.In order to improve the working stability of loading machine,a reasonable control mode of input motion to the driving link is proposed.